Improved embedded wideband speech codec fitting EV-VBR standard - XIN Jie; BAO Chang-chun; JIA Mao-shen; LIU Xin (Tongxin xuebao)
Based on the International Telecommunication Union Telecommunication Standardization Sector（ITU-T） recommendation for EV-VBR coding standard and the candidate codec designed by Speech and Audio Signal Processing Laboratory（SASPL） of Beijing University of Technology,an improved embedded variable bit rates wideband speech codec was proposed.In the improved codec,ACELP coding was implied to the first two coding layers.The middle sub-frame spectral parameters were computed and quantized.Three pulses depth first tree search algorithm was designed.On the higher three coding layers embedded TCX coding was reconstructed by accumulating frequency coefficients vectors.Addition-ally,VAD and DTX functions were implemented in the improved codec.Test results show that the improved codec achieves better speech quality and much lower coding complexity than the original codec.The speech quality and coding efficiency are comparable with G.718 of a new ITU-T speech coding standard and the low delay feature is retained.